Eksplorasi Minat Masyarakat dalam Menggunakan Electronic Money Card Melalui Pendekatan TAM-TPB - Defi Insani Saibil; Novita Dwi Rachmawati (Journal of Islamic Economic Scholar, 2026)
This study aims to examine the factors influencing consumers’ intention to use Electronic Money Cards in the Greater Jakarta area (Jabodetabek) by integrating the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB). A quantitative research approach was employed using an online survey of 257 Electronic Money Card users, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The findings indicate that perceived usefulness and perceived ease of use have positive and significant effects on attitude toward using, while perceived ease of use also positively influences perceived usefulness. Furthermore, attitude toward using, subjective norm, and perceived behavioral control significantly affect intention to use, whereas perceived usefulness does not have a significant direct effect on intention to use. These findings suggest that improving the ease of use of Electronic Money Cards, fostering positive user attitudes, strengthening social influence, and enhancing users’ perceived behavioral control are essential strategies for increasing consumers’ intention to use this payment instrument. This study contributes to the digital payment literature by integrating TAM and TPB to explain consumers’ intention to use Electronic Money Cards, a payment technology that has received relatively limited scholarly attention compared with e-wallets, QR-based payments, and mobile banking, thereby extending the application of technology adoption theories in the Indonesian digital payment context. Keywords : Electronic Money Card, Technology Acceptance Model (TAM), Theory of Planned Behavior (TPB)